Numbered days : diaries and the Holocaust - Garbarini, Alexandra, 1973- (Yale University Press, 2006)
As the Nazis swept across Europe during World War II, Jewish victims wrote diaries in which they grappled with the terror unfolding around them. Some wrote simply to process the contradictory bits of news they received; some wrote so that their children, already safe in another country, might one day understand what had happened to their parents; and some wrote to furnish unknown readers in the outside world with evidence against the Nazi regime. Were these diarists resisters, or did the process of writing make the ravages of the Holocaust even more difficult to bear? Drawing on an astonishing array of unpublished and published diaries from all over German-occupied Europe, historian Alexandra Garbarini explores the multiple roles that diary writing played in the lives of these ordinary women and men. A story of hope and hopelessness, "Numbered Days" offers a powerful examination of the complex interplay of writing and mourning. And in these heartbreaking diaries, we see the first glimpses of a question that would haunt the twentieth century: can such unimaginable horror be represented at all?